Aabrm1-mediated melanin synthesis is essential to growth and development, stress adaption, and pathogenicity in Alternaria alternata - Li, Rong; Li, Yongcai; Xu, Wenyi; Liu, Wenjuan; Xu, Xiaobin; Bi, Yang; Prusky, Dov (Frontiers in Microbiology, 2024)
Scytalone dehydratase (brm1) is one of the key enzymes in 1, 8-dihydroxynaphthalene (DHN) melanin synthesis, which mediated melanin biosythesis regulates cell biological process of plant fungi, but its function in Alternaria alternata, the causal agent of pear black spot, is unclear. Brm1 in A. alternata was cloned, identified and named as Aabrm1. An Aabrm1-deletion mutant was generated and revealed that the Aabrm1 deletion leads to significant decrease in melanin production, and form orange colony smooth spores. In addition, deletion of Aabrm1 gene impaired infection structure information and penetration. The external stresses resistance of ΔAabrm1 was significantly weakened, in particular, it is very sensitive to oxidative stress, and the contents of H2O2 and O2 .-in the ΔAabrm1 were significantly increased. Virulence of ΔAabrm1 was reduced on non-wound-inoculated pear leaves but not changed on wound-inoculated on pear fruit. These results indicated that Aabrm1 mediated melanin synthesis plays an important role on pathogenicity of A. alternata.